Research and Innovations Strategic Plan 2020/21 - 2024/25 - Kabale University (Kabale University, 2023)
Research and Innovations Strategic Plan 2020/21 - 2024/25. facilitate RISP partnerships and collaborations with other universities and research organizations in Uganda and abroad to increase the visibility of RISP activities at KAB. Over the next five years, Research and Publications at Kabale University will focus on implementing the University’s research agenda. Through the research agenda, Kabale University will aim to contribute to local, national as well as international development agendas to demonstrate the relevance of the University to society. The plan has six strategic objectives: ⁃ Strengthen and streamline the governance of research and innovations at KAB; ⁃ Build and retain a highly effective research workforce and culture; ⁃ Identify and mobilize funds for research and innovation activities; ⁃ Increase the quantity and impact of research and innovation; ⁃ Build resilient, sustainable, and productive research collaborations; ⁃ Create an enabling environment for research and innovations.